2015
DOI: 10.5604/00441600.1146845
|View full text |Cite
|
Sign up to set email alerts
|

Problem Kapitalizacji Subsydiów W Rolnictwie

Abstract: WstępCelem artykułu jest potwierdzenie tezy, że zagadnienie kapitalizacji subsydiów występuje i zarazem nie jest ono wystarczająco szeroko przeanalizowane w dotychczasowych badaniach naukowych. Zjawisko to wymaga wieloaspektowego scharakteryzowania i oszacowania jego oddziaływania na gospodarkę krajową i unijną, gdyż stanowi istotny i znaczący efekt uboczny interwencjonizmu w rolnictwie. Autorzy dokonali przeglądu dorobku amerykańskich i europejskich naukowców 1 , a następnie zobrazowali analizowane zjawisko p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…This is evidenced by a sharp growth in rental fees from the moment of obtaining the status of beneficiaries of Common Agricultural Policy of the European Union by the Polish farmers. Góral and Kulawik (2015) argue that this distorts the idea of support, because it was presupposed that direct payments were to improve and stabilise the professional situation of "professionally active farmers", while they largely go to landowners, who are not professionally active farmers and leased their land, as increased land rent. The described phenomenon is sometimes termed as "outflow of budgetary support".…”
Section: Valorisation Of Agricultural Land -Input Income and Hedonicmentioning
confidence: 99%
“…This is evidenced by a sharp growth in rental fees from the moment of obtaining the status of beneficiaries of Common Agricultural Policy of the European Union by the Polish farmers. Góral and Kulawik (2015) argue that this distorts the idea of support, because it was presupposed that direct payments were to improve and stabilise the professional situation of "professionally active farmers", while they largely go to landowners, who are not professionally active farmers and leased their land, as increased land rent. The described phenomenon is sometimes termed as "outflow of budgetary support".…”
Section: Valorisation Of Agricultural Land -Input Income and Hedonicmentioning
confidence: 99%
“…Hence, there is no "sample" involved. 10 On the other hand it might be concluded that the data for all objects in the population do nonetheless constitute a sample, but a "sample from the repeatability of the phenomenon". The explained flows of rents through prices are an effect both of main causes and of subsidiary (random) causes, which give the model a stochastic character.…”
Section: Methodsmentioning
confidence: 99%
“…The receipt of area payments, however, is little dependent on reductions in the use of environmentally harmful chemicals or over-intense agricultural production. Moreover, although direct payments were intended to improve the economic situation of professionally active farmers, they are largely transferred, through increased rental prices, to landowners who are not professionally active in agriculture but merely lease their land (Góral, Kulawik 2015). On the other hand, programmes under the second pillar of the CAP are oriented towards not only the development of agriculture, but also that of rural areas in a wider sense, and in the authors' view these make a greater contribution to the creation or conservation of public goods (or more precisely, common goods; cf.…”
Section: Public Goods In the Capmentioning
confidence: 99%
“…In the literature, studies on the accumulation of assets often relate to the capitalization of agricultural support. As shown by the research results (Swinnen and Vranken, 2009;Góral and Kulawik, 2015) the direct payments under the CAP are capitalized in the rates of land lease, price of land and other fixed assets. In this way, accumulation is considered as the effect of direct payments support.…”
Section: Introductionmentioning
confidence: 99%